Efectos del fertilizante edáfico en diferentes dosis, en el cultivo de arroz en el Cantón Babahoyo - Ruiz Tapia, Antony Nelson (2020)
This research work was carried out in the El Porvenir - Babahoyo Canton, Pimocha Parish, Los Rios province, located at km 12 of the Babahoyo - Jujan road, between the geographic coordinates 79 ° 37'59 ”UTM of longitude West and 10 ° 52'22 ”UTM south latitude; with a height of 7 m.s.n.m. The area has a humid tropical climate, with an average annual temperature of 24.7 ° C; annual precipitation 1976 mm; relative humidity 85% and 998.2 hours of heliophany annual average. The Iniap-14 variety was used as planting material. The treatments included Nutriesencial ® at a dose of 200 kg/ha, Nutriesencial ® at a dose of 250 kg/ha, Nutriesencial ® at a dose of 300 kg/ha, Nutriesencial ® at a dose 350 kg/ha, Nutriesencial ® in a dose of 400 kg/ha, Nutriesencial ® in a dose of 450 kg/ha, Conventional fertilization N - P - K - S in a dose of 275 kg/ha, Farmer Witness N - P - K - S in a dose of 187 kg/ha. Regarding the treatments used in the present investigation, it is observed that conventional fertilization and farmer fertilization reached the highest yields in relation to the other treatments. Nutricencial treatment in doses of 400 kg ha-1 was economically favorable. Weed control is recommended before the fertilizer application time.